Learner experiences of identity and global interdependence following engagement with an interprofessional education course. - Manspeaker, Sarah A.; Oerther, Sarah; Pole, David; Cobb, Haley; Breitbach, Anthony (Journal of Interprofessional Care)
University core curricula and accreditation standards for healthcare profession programs can be challenging to align. Additionally, interprofessional education (IPE) requirements for healthcare professions curricula have been designed to prepare learners for future practice. This paper describes alignment of an introductory IPE course with embedded Interprofessional Education Collaborative core competencies to specific university Core Curriculum attributes. A cross-sectional, mixed methods design was used to examine 117 learners' reflections on the IPE course content and learning outcomes. Learners from seven pre-licensure health professions programs provided responses on aspects of their IPE learning experience through reflections, surveys, written examinations, and optional focus groups. Open-ended responses were interpreted thematically from a constructivist lens. Results revealed positive perceptions of the course with feedback for areas of consideration for future course activities. Learners reported more engagement with the Core Curriculum attribute of Identities in Context than that of Global Interdependence. Additionally, responses indicated a perception of task work versus teamwork within the interprofessional team activities. Outcomes provided data that enabled continuous quality improvement of the course. Educators seeking to align IPE courses with institutional core curricula and accreditation standards may use this work to inform structure, assessment, and delineation of teamwork as compared to task work.